Cloacal Exstrophy Repair with Primary Closure of Bladder Exstrophy: A Case Report and Review of Literature - George Bethell; Navroop Johal; Peter Cuckow (Case Reports in Pediatrics)
Cloacal exstrophy is the most complex congenital, ventral, abdominal wall defect. Traditionally surgery consists of a staged approach to repair which takes place on many separate theatre visits. In this case a primary approach was undertaken resulting in a relatively short inpatient stay and a reduced risk from multiple surgical procedures under general anaesthesia.